Financial Development and Export Concentration - Florian Unger (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper analyzes the impact of financial development on export concentration. I incorporate credit constraints into a trade model with heterogeneous exporters and endogenous quality choice. The model predicts that financial development increases innovation activity and export shares of larger firms. In contrast, a model variant in which exporters have to finance production costs instead of investments suggests a negative impact of financial development on export concentration as smaller firms benefit more from relaxing credit constraints. These opposing predictions are tested using export data for 70 countries over the period 1997-2014 and exploiting variation in external finance dependence across sectors. I find strong support for the predictions of the investment model that higher financial development increases export concentration among top firms, especially in sectors with high external finance dependence and large scope for quality differentiation. This effect is also present within firms: financial development induces exporters to skew their sales towards the top performing products. I finally show in a counterfactual analysis that financial frictions are quantitatively important to explain the variation in the skewness of exports across countries and sectors.
Keywords: F12; F14; G32; L11; 330; international trade; superstar firms; export concentration; external finance; credit constraints; financial development; innovation